Pengaruh Diskusi Kelompok dalam Model Discovery Learning Terhadap Hasil Belajar IPA - Viona Salsabila; M. Thoha B. S. Jaya; Ujang Efendi (Universitas Lampung, 2020)
The problem in this research was the student’s result of IPA in the thematic learning at Jatimulyo Elementary School 3 are still low. The purpose of this study was to find out 1) the comparison of IPA learning outcomes in thematic learning using discovery learning models more effectively compared to those using conventional learning, and 2) the effect of group discussions in discovery learning models on IPA learning outcomes. The type of research used is experimental research with the research design is nonequivalent control group design. The population of this research were all fifth grade students of SDN 1 Jatimulyo, SDN 2 Jatimulyo, and SDN 3 Jatimulyo. The research sample was the fifth grade students of SDN 3 Jatimulyo. The sampling technique used multistage random sampling technique. Data collection techniques used observation and tests. Data analysis used simple linear regression test and t-test. Based on the results of hypothesis analysis was that1) the results of IPA learning in thematic learning that used the discovery learning model are more effective than those using conventional learning, and 2) the group discussion in the discovery learning model effected to the student’s IPA result in thematic learning.Keywords: discovery learning, group discussion, and IPA learning outcomes DOI: http://dx.doi.org/10.23960/jiip.v2i1.21791